Auditory Cortex Morphology Predicts Language Learning Potential in Children and Teenagers - Turker, Sabrina; Reiterer, Susanne Maria; Schneider, Peter; Seither-Preisler, Annemarie (Frontiers in Neuroscience, 2019)
In two recent studies, we identified neuroanatomical and neurofunctional markers of musical aptitude, attention deficit (hyperactivity) disorder and dyslexia in the auditory cortex (AC) of children. In a subsequent study with adults, we found evidence for neuroanatomical correlates of speech imitation ability in right Heschl‘s gyrus (HG), a structure comprising primary and parts of secondary AC. In the present study, we aimed to verify this previously suggested link between structural variation of right HG and language aptitude in a younger population of children and teenagers (N=42; age range: 10-16 y), while behaviorally exploring the relationship between language aptitude, working memory, arithmetic skills and musicality. Behaviorally, scores on the language aptitude battery strongly correlated with working memory and speech imitation ability. Furthermore, we found that self- and parent-reported language aptitude and school grades were closely associated with language aptitude scores. Neuroanatomical analyses revealed a significant relationship between the occurrence of multiple HGs and high grey matter (GM) volumes in right AC and high language aptitude regardless of age, gender or musical ability. Additionally, low language aptitude correlated significantly with the occurrence of single gyri in right AC. In accordance with previous research, we suggest that right HG might be associated with language aptitude, with a stronger gyrification and higher GM volumes being beneficial for successful auditory processing and the integration of speech-related cues.